Chronic endometritis multiplies the recurrence risk of endometrial polyps after transcervical resection of endometrial polyps: a prospective study - Jing Huang; Xiao You; Zijun Zhao; Xiaorui Jiang; Dacheng Qu (BMC, 2024)
Abstract Background To investigate the impact of chronic endometritis (CE) on the recurrence of endometrial polyps (EPs) in premenopausal women after transcervical resection of endometrial polyps (TCRP). Methods This prospective study enrolled 507 women who underwent TCRP between January 1, 2022 and December 31, 2022. The patients were divided into a CE group (n = 133) and non-CE group (n = 374) based on the expression of CD138 in the endometrium. The EP recurrence rate at 1 year after TCRP was compared between the CE and non-CE groups and between groups with mild CE and severe CE. The impact of CD138 expression by resected EPs on EP recurrence also was investigated. Results The EP recurrence rate at 1 year post-TCRP was higher in the CE group than in the non-CE group (25.6% vs. 10.4%) and also higher in the severe CE group than in the mild CE group (34.5% vs. 18.7%). Additionally, the EP recurrence rate was higher among patients with CD138-expressing EPs than among those with EPs lacking CD138 expression (30.5% vs. 6.5%). The odds ratio (OR) for EP recurrence in the CE cohort compared with the non-CE cohort was 3.10 (95% confidence interval [CI] 1.84-5.23) after adjustment for EP number and precautions against EP recurrence. The ORs for EP recurrence in patients with mild CE and severe CE were 2.21 (95%CI 1.11-4.40) and 4.32 (95%CI 2.26-8.26), respectively. Similarly, the OR for EP recurrence in cases with CD138-expressing EPs relative to cases with EPs lacking CD138 expression was 6.22 (95%CI 3.59-10.80) after adjustment for EP number and precautions against EP recurrence. Conclusions CE multiplied the recurrence rate of EPs in premenopausal women after TCRP, and this effect positively correlated with CE severity. CD138 expression by EPs also was associated with a higher risk for EP recurrence.